High-flow arteriovenous fistula and myocardial fibrosis in hemodialysis patients with non-contrast cardiac magnetic resonance imaging - Choi, Yong Seon; Lee, In Jae; An, Jung Nam; Song, Young Rim; Kim, Sung Gyun; Lee, Hyung Seok; Kim, Jwa-Kyung (Frontiers in Cardiovascular Medicine, 2022)
Background The role of high-flow arteriovenous fistula (AVF) in cardiovascular morbidity in hemodialysis (HD) patients is very likely under-recognized. We assessed the relationship between high access flow (Qa) and myocardial fibrosis in HD patients. Methods Myocardial fibrosis was assessed by native T1 relaxation times on non-contrast cardiac magnetic resonance imaging and a potential marker of fibrosis. Serum levels of galectin-3, N-terminal pro-B-type natriuretic peptide (NT-proBNP), and monocyte chemoattractant protein 1 (MCP-1) were measured in 101 HD patients who underwent regular monitoring of AVF Qa. A high-flow AVF was defined as a Qa >2 L/min. Results Hemodialysis patients showed significantly higher galectin-3 value and increased T1 relaxation time compared to healthy volunteers, suggesting increased myocardial fibrosis in uremic cardiomyopathy. In HD patients, 20 (19.8%) had a Qa > 2L/min, and they had significantly higher cardiac output, cardiac index, left ventricular mass, and increased T1 times than those with a Qa ≤ 2 L/min. Also, serum galectin-3 and NT-proBNP levels were much higher in the high Qa group, indicating a close relationship between the high Qa, increased myocardial fibrosis, and the risk of heart failure (HF) in HD patients. It is interesting that a higher AVF Qa for myocardial fibrosis was independent of several traditional cardiovascular risk factors as well as serum levels of NT-proBNP and MCP-1. Conclusions A supra-physiologically high Qa can be related to myocardial fibrosis and increased risk of HF in HD patients. Regular Qa monitoring could allow early detection of a high-flow AVF that could arise cardiac complications.